STRATEGI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK PROVINSI RIAU DALAM MEMPEROLEH PENGHARGAAN PENGGERAK PROVINSI LAYAK ANAK TAHUN 2019 - Ardila Sari; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the strategy of the Riau Province Women's Empowerment and Child Protection Office in obtaining the 2019 Child Eligible Province mover award and the inhibiting and supporting factors in the Riau Province Women's Empowerment and Child Protection Office in obtaining the 2019 Child Eligible Province mover award.The location of the research was carried out at the Office of Women's Empowerment and Child Protection in Riau Province. This study involved 5 informants, namely the Head of Women's Empowerment and Child Protection, Staff for Women's Empowerment and Child Protection, Secretary of the Riau Province Women's Empowerment and Child Protection Office, Pekanbaru City KLA Cluster Team and other KLA cluster teams. Data collection techniques used in this research are interviews, documentation and literature. The data analysis technique used in this study uses interactive analysis which includes three components: (1) data reduction, (2) data presentation, (3) drawing conclusions.The results of this study: (1) The strategies adopted by the Riau Province Women's Empowerment and Child Protection Service in the Development of Eligible Children in Riau Province in Riau Province in 2019 there are three (3) strategies, diversification strategies, preventive strategies and innovative strategies. (2) The inhibiting factors of the Riau Province Office of Women's Empowerment and Child Protection in the Development of Child Friendly Provinces in Riau Province are first, the lack of socialization to the community. Second, budget constraints, and third, the lack of community participation. (3) The supporting factors of the Riau Province Women's Empowerment and Child Protection Service in the Development of Child Friendly Provinces in Riau Province are first, the existence of collaboration with SKPD and second, the community as an intermediary. Keywords: strategy, coordination, and DPPPA.